2014
DOI: 10.1007/s11274-014-1633-0
|View full text |Cite
|
Sign up to set email alerts
|

Shift of bacterial community structure in two Thai soil series affected by silver nanoparticles using ARISA

Abstract: In this study we examined the influence of silver nanoparticles (SNP) on the bacterial community and microbial processes in two soils from Thailand, a Ayutthaya (Ay) and Kamphaengsaen soil series (Ks). Results of this analysis revealed that SNP did not affect to pH, electrical conductivity, cation exchange capacity, and organic matter in both the Ay and Ks series. Automated ribosomal intergenic spacer analysis (ARISA) analysis profiles showed that bacterial community decreased with increasing SNP concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Also, Anjum et al (2013) and Dimkpa (2014) stated that the antimicrobial properties of AgNPs can get altered when released in soil due to the undergoing complex array of biotic and abiotic processes, for example, pore water harbors a range of electrolytes that increase the aggregation of AgNPs in soil, thus reducing its size-dependent toxicity (Lee et al 2012). The dose-dependent effect of AgNPs on soil microbial community was also reported by Chunjaturas et al (2014). Sillen et al (2015) in their study suggested a link in increased biomass in maize only when there was a change in soil bacterial community, indicating that the microbial population was altered in a way to promote plant growth.…”
Section: Resultssupporting
confidence: 76%
“…Also, Anjum et al (2013) and Dimkpa (2014) stated that the antimicrobial properties of AgNPs can get altered when released in soil due to the undergoing complex array of biotic and abiotic processes, for example, pore water harbors a range of electrolytes that increase the aggregation of AgNPs in soil, thus reducing its size-dependent toxicity (Lee et al 2012). The dose-dependent effect of AgNPs on soil microbial community was also reported by Chunjaturas et al (2014). Sillen et al (2015) in their study suggested a link in increased biomass in maize only when there was a change in soil bacterial community, indicating that the microbial population was altered in a way to promote plant growth.…”
Section: Resultssupporting
confidence: 76%
“…Notwithstanding the analytical approach used, physical properties of soil are known to modulate the effect of NPs as described here. Effect of S-NPs on bacterial communities of two soils from Thailand was studied using ARISA ( Chunjaturas et al., 2014 ). Different concentrations of S-NPs were employed – 50, 100, 250, and 500 μg/g soil and incubation periods were 2, 4 and 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Based on findings of such studies it has been anticipated that the denitrifying bacterial community is assumed to be highly susceptible to nanoparticles toxicity (Throbäck et al, 2007; VandeVoort and Arai, 2012). Despite the clearly known impact of nanoparticles on soil microbial community, there exists a dearth of literature providing apparent connection between soil factors and toxic behavior of nanoparticles toward soil biota (Calder et al, 2012; Chunjaturas et al, 2014; Shah et al, 2014; Mishra and Singh, 2015a). In this context, Frenk et al (2013) evidenced effect of copper oxide (CuO) and magnetite (Fe 3 O 4 ) nanoparticles on soil bacterial community in two different soil types (sandy loam and sandy clay loam).…”
Section: Concerning Risk Assessment Factors and Their Modulation For mentioning
confidence: 99%